Designing a Model for Implementing Human Resource Strategies in the Field of Health - Moradi, Mojtaba; Haj Alian , Farshad; Jahangirfard, Majid; Mehdizadeh Ashrafi , Ali (Iranian Journal of Educational Sociology, 2022)
Purpose: One of the main organizational planning is human resource planning. The purpose of this study was to design a model for the implementation of human resource strategies in the field of health.Methodology: The combined research method and research design were also of the type of mixed exploratory research design. In the qualitative section, using the method of "samples contain rich information" with 20 heads of medical universities and senior managers of the Ministry of Health and Medical Education, using the Delphi method and using semi-structured questionnaires; Was interviewed. In the quantitative part of the research, a researcher-made questionnaire with multi-stage relative stratified sampling method was distributed among 334 senior and middle managers of the country's medical universities and the data were used by exploratory and confirmatory factor analysis. Analyzed with SPSS and AMOS software.Findings: The results indicate that "human resource strategies" have six dimensions: 1. Human resource provision, 2. Training, 3. Performance evaluation, 4. Development and improvement, 5. Service reward and 6. Participation And "strategy implementation" has three dimensions and nine components as described: a- Structural dimension (1. structure of the implementing organization, 2. Capacities, 3. Resources), b- Environmental dimension (4. Macro environment, 5. Intermediate environment 6. Execution environment) and c- Behavioral dimension (7. Performers 'behavior, 8. Target community behavior and 9. Developers' behavior). The results of the quantitative section showed that the impact of all dimensions of human resource strategies on the structural, environmental and behavioral dimensions of strategy implementation was confirmed.Conclusion: Special attention to human resources, especially in organizations providing health services and health in the community as the most vital element of organizational success and creating a sustainable competitive advantage is always important in management.